2014
DOI: 10.4103/0019-509x.152001
|View full text |Cite
|
Sign up to set email alerts
|

Two-incision approach for video-assisted thoracoscopic sleeve lobectomy treating the central lung cancer

Abstract: Video-assisted thoracoscopic surgery sleeve lobectomy with bronchoplasty is a feasible and safe surgical approach, using only two incisions. This way of operation can promote the development of surgical technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Although video-assisted thoracic surgery (VATS) is regarded as a minimally invasive procedure with good long-term survival outcomes [ 5 ], many surgeons considered that sleeve resection was an absolute contraindication for VATS lobectomy due to oncological concerns in obtaining a complete resection and technical complexity. Therefore, there are few reports in the literature of VATS sleeve lobectomy for lung cancer in recent years [ 6 14 ]. In addition, the purported benefits of VATS over thoracotomy in performing sleeve lobectomy have only been reported in series using only one surgical approach or in single case reports.…”
Section: Introductionmentioning
confidence: 99%
“…Although video-assisted thoracic surgery (VATS) is regarded as a minimally invasive procedure with good long-term survival outcomes [ 5 ], many surgeons considered that sleeve resection was an absolute contraindication for VATS lobectomy due to oncological concerns in obtaining a complete resection and technical complexity. Therefore, there are few reports in the literature of VATS sleeve lobectomy for lung cancer in recent years [ 6 14 ]. In addition, the purported benefits of VATS over thoracotomy in performing sleeve lobectomy have only been reported in series using only one surgical approach or in single case reports.…”
Section: Introductionmentioning
confidence: 99%
“…Ceylan et al reported that, in their series of 12 cases, there was one case of myocardial infarction and one case of prolonged air leak [5]. Wang et al reported that there were no complications in their series [6]. The complications of our cases were as follows: in the first case, minimal subcutaneous emphysema was detected but did not require intervention, and in the second case, partial atelectasis occurred, which improved with bronchoscopic secretion aspiration.…”
Section: Discussionmentioning
confidence: 56%
“…The disadvantage of VATS sleeve lobectomy is that the duration of the anastomosis is longer than thoracotomy. Zhou et al and Wang et al reported mean durations of anastomosis between 55 and 39 minutes, respectively [3,6]. In Ceylan et al the reported range of anastomosis time was 55-110 minutes [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation